Some questions of responsibility of criminal participants under the legislation of the Republic of Kazakhstan - Ozbekov, D.O.; Kalguzhinova, А.М.; Galy, Zh.O. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
The article is devoted to a theoretical review of the regulation of the ground for criminal liability of the accomplices of a criminal offense. The current Criminal Code of the Republic of Kazakhstan of 2014 largely retained the norms of criminal law of 1997 (understanding of participation, types of accomplices, grounds and limits of their responsibility). To determine the current state of counteraction to criminal offenses, committed in complicity, the authors conducted a comparative study of the norms of the Criminal Code of the Republic of Kazakhstan of 1997 and the Criminal Code of the Republic of Kazakhstan of 2014. The object of the study is the effectiveness of countering criminal offenses, committed in complicity, based on the analysis of domestic investigative and judicial practice for the period of 2015-2018. The subject of the study is the rules on the types of accomplices in a criminal offense and their responsibility. The aim of the study is to develop an effective model for countering criminal offenses, committed by the group. Responsibility of accomplices is based on the principles of independent and strictly individual responsibility for the committed act. In article 28 of the Criminal Code the nature of the criminal acts of each identified accomplice in it is clearly differentiated. Considering the interdisciplinary nature of the studied problem, the author used dialectical, formal and logical, comparative and legal, statistical, historical and legal research methods. The empirical base of the study was compiled by the statistical data of the Committee on Legal Statistics and Special Accounts of the General Prosecutor's Office, information materials of the Supreme Court (procedural documents of the Judicial Office service, «Taldau» forum) of the Ministry of Internal Affairs of the Republic of Kazakhstan. Direct analysis of investigative judicial practice allowed the authors to offer a number of scientifically based recommendations for improving criminal law and improving the work of law enforcement agencies.
Қазақстан Республикасының заңнамасы бойынша қылмысқа қатысушылардың жауаптылығының кейбір сұрақтары
Некоторые вопросы ответственности соучастников преступления по законодательству Республики Казахстан
Keywords: complicity in a criminal offense; performer; organizer; instigator; accomplice; criminal and law and criminological features; responsibility of accomplices